Eugenics in the ancient Indian culture of Aryan tribes - Gregory Tsoucalas; Halil Tekiner; Konstantinos Markatos; Marianna Karamanou; Theodoros Papaioannou (Academy of Sciences of Moldova, 2018)
During 1500 BC the nomadic tribes of the Aryan people migrated to the Indian subcontinent. They strongly believed in their superiority above the local inhabitants, and raised social barriers to create a perfect race. The ideal family and the birth (motherhood) of a son, as an offspring to continue father's presence in earth, were of great importance. The union of a perfect couple, man and wife, was sacred. Ayurveda, which literally means "knowledge of life» was infiltrated in religion. Thus, Aryans divinised their views and eugenics conquered their minds, helped them to survive and at the end drove them to isolation, becoming their doom.